Bringing Order Out of Chaos: Stanisław August Poniatowski's Political Patronage of Architectural Classicism in the Late Eighteenth-Century Polish-Lithuanian Commonwealth. (3rd July 2018) - Getka-Kenig, Mikołaj
ABSTRACT: This article examines the political uses of classical architecture in the late eighteenth-century Polish-Lithuanian Commonwealth. It focuses specifically on the direct connection between the rise of the classical idiom on the eve of the collapse of the Commonwealth and the ill-fated idea of political recuperation of the deteriorating and dysfunctional state under the aegis of King Stanisław August Poniatowski (r. 1764–95). In particular, it outlines the extent and character of Polish-Lithuanian architectural classicism's political engagement in the last decades of the eighteenth century. It also underscores the specific role of this architectural idiom as a political symbol and instrument of propaganda, which served to represent the idea of restoring political order to the Commonwealth and building a strong and self-sustaining political community headed by the king. Finally, it presents a selection of characteristic buildings and publications that contributed to this political discourse, and examines the ways classical architecture retained a political importance in the immediate aftermath of the destruction of the Polish-Lithuanian Commonwealth in 1795.